Histoenzymic studies on testis following oral zinc supplementation in Assam male goats - DEVI, J; GOSWAMI, J; SARMAH, B C; SARMA, K; BHATTACHARYA, M (The Indian Journal of Animal Sciences, 2012)
Studies were conducted to ascertain the effect of organic and inorganic forms of oral zinc supplementation on the histoenzymology of the testis in Assam goats of 3 to 7 months of age. It revealed that the histoenzymic activity of different tissue enzymes like LDH, MDH, D5-3 ß- hydroxysteroid dehydrogenase and 17-ß-hydroxysteroid dehydrogenase in the Leydig cells of the testis increased with advancing age in all the groups, but comparatively higher activities of this enzyme were observed in the zinc-supplemented groups than that of control.